Điều tra về mức độ hiệu quả của việc sử dụng video có phụ đề để dạy kỹ năng nghe cho sinh viên chuyên tiếng Anh năm thứ nhất, trường Cao đẳng Sư phạm Thái Bình. - Trần, Thị Hiền (Đại học Quốc gia Hà Nội, 2017)
This action research examines the effectiveness of using subtitled/ captioned videos in teaching listening skillto elementary students and explores the students‟ attitudes towards this kind of listening activity. The study was conducted at Thai Binh Teacher Training College in 2016 within nine weeks. Ten first-year students in one class were involved in the study. Different data sources, viz. pre-tests, post-tests, progress tests, journal writing; and interviews were analyzed in triangulation with one another. The findings reveal that using subtitled/captioned videos potentially has positive effects on listening in terms of listening comprehension, vocabulary acquisition, especially of the students who took notes while watching videos, and fostering students‟ interests and motivation. However, sometimes subtitles/captions make students feel distracted because they had to watch the videos, listen to the sound and read the subtitles at the same time. Accordingly, implications for appropriate video selection,and process and procedure of using videos with subtitles are proposed